International Justice for Atrocity in Africa?The International Criminal Court,African Governments and Sustainable Peace - (:unkn) unknown (My University, 2011)
The action of the International Criminal Court (ICC) in Africa is often criticized for its partiality and as being a tool in the handsof a hegemonic neocolonialism. Despite those critics, which are sometimes caricatural, the analysis of the intervention ofthe first permanent institution for international criminal justice is crucial to understand the dilemma and contradictions arisingbetween the theory and the practice of transitional justice. This paper will discuss the role of the International CriminalCourt (ICC) in Africa, with particular reference to the process of Transitional Justice (TJ) in Burundi. The main topics of thispaper consider the relationship between the ICC and the peace-justice dilemma, as well as critical analysis of this peace-justicedichotomy in light of TJ processes more broadly.
Keywords: African Research